2013
DOI: 10.1016/j.jaac.2012.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Gender Nonconformity, Bullying Victimization, and Depressive Symptoms Across Adolescence and Early Adulthood: An 11-Year Longitudinal Study

Abstract: Objective Childhood gender nonconformity has been associated with increased risk of caregiver abuse and bullying victimization outside the home, but it is unknown whether as a consequence children who are nonconforming are at higher risk of depressive symptoms. Method Using data from a large national cohort (N = 10,655), we examined differences in depressive symptoms from ages 12 through 30 years by gender nonconformity before age 11 years. We examined the prevalence of bullying victimization by gender nonco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
165
3
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 222 publications
(192 citation statements)
references
References 41 publications
13
165
3
4
Order By: Relevance
“…The finding regarding gender atypicality was consistent with previous research showing that higher levels of self-reported gender non-conformity are linked to higher levels of self-reported stress and anxiety among both homosexual and heterosexual males, above and beyond sexual orientation (Alanko et al, 2009,Lippa, 2008Rieger & Savin-Williams, 2012;Roberts et al,2012Roberts et al, , 2013. While this study did not examine mechanisms, one reasonable hypothesis is that gender-atypicality leads to higher lifetime rates of experiencing rejection and victimization.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The finding regarding gender atypicality was consistent with previous research showing that higher levels of self-reported gender non-conformity are linked to higher levels of self-reported stress and anxiety among both homosexual and heterosexual males, above and beyond sexual orientation (Alanko et al, 2009,Lippa, 2008Rieger & Savin-Williams, 2012;Roberts et al,2012Roberts et al, , 2013. While this study did not examine mechanisms, one reasonable hypothesis is that gender-atypicality leads to higher lifetime rates of experiencing rejection and victimization.…”
Section: Discussionsupporting
confidence: 90%
“…Some have suggested that what places homosexuals at risk is less their sexual orientation per se and, more, their gender nonconforming behavior (Rieger & Savin-Williams, 2012;Roberts, Rosario, Slopen, Calzo, & Austin, 2013). Research has shown that homosexual men are more likely to exhibit atypical gender behaviors such as dressing, speaking or walking in an effeminate manner (Lippa, 2000(Lippa, , 2005(Lippa, , 2008Rieger, Linsenmeier, Gygax, & Bailey, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Stotzer, 2009), but the present study extends this to nonbinary youth. A general population study found that the relationship between gender nonconformity during childhood and depressive symptoms in early adulthood was partly mediated by caregiver abuse (Roberts et al, 2013). The relationship between childhood gender conformity and gender identity, child abuse and psychological problems requires investigation in gender minority samples, including nonbinary individuals.…”
Section: Abuse and Violencementioning
confidence: 99%
“…65 Obese children are often bullied and can have associated decreased mobility, thus, presenting with higher levels of internalizing symptoms secondary to their appearance (each of which can lead to the other). 66,67 More severe OSA was found among obese children than normal-weight children with OSA and those with PS. 57,68 Depressive symptoms were also significantly higher in the obese group than the other 2 groups.…”
Section: Discussionmentioning
confidence: 98%